Impact of vegetation types on the floristic diversity, the availability and the ecological characteristics of five woody species stands used in the management of hypertension and diabetes in southern Burkina Faso. - Compaoré, Souleymane; Hounkpevi, Achille; Zerbo, Issouf; Belemnaba, Lazare; SALAKO, Kolawolé Valère; Gbemavo, Charlemagne; Ouédraogo, Sylvin; THIOMBIANO, Adjima (My University, 2021)
The use of modern drugs to manage hypertension and diabetes is enough expensive and requires constant monitoring of the patient due to the chronicity and complications of these diseases. Thus, the populations of southern Burkina Faso have opted for the use of plants, including Parkia biglobosa (Jacq.) R.Br. ex G. Don, Sclerocarya birrea (A. Rich.) Hochst, Lannea acida A. Rich, Lannea microcarpa Engl. & K. Krause and Balanites aegyptiaca (L.) Delile. To better contribute to preserving these fve target species, the present study analyses the foristic diversity of the diferent vegetation types in which they occur, assesses their availability and determines the health status of their stands. To achieve this, a foristic inventory was conducted in 109 plots, including 26 plots of 500 m2 in riparian forests, 22 of 2500 m2 in fallows 31, 18 and 12 of 1000 m2 in tree savannahs, shrub savannahs and fenced areas, respectively. The diameter at breast height (dbh) of each individual of the target species was measured in each plot and its health status assessed. Results showed that species diversity varied signifcantly among vegetation types. According to the Shannon index, riparian forests were the most diversifed (H=2.62±0.02 bits). Lannea microcarpa, Lannea acida, Sclerocarya birrea, and Balanites aegyptiaca were very frequent (Ri≤60) to moderately frequent (60<Ri<80) within vegetation types. The vitality of their stands was independent of vegetation types. However, their individuals were weakly attacked in the fenced areas indicating that local people control these ecosystems. Fenced areas strategies appear to be alternative solutions to preserve stands of species that are an mostly high priority for populations.
Keywords: Woody vegetation; Sustainable preservation; Hypertension; Diabetes